Revitalisasi Pentasharufan Dana Zakat, Infak, dan Sedekah Dalam Meningkatkan Kesejahteraan Umat Menggunakan Konsep Three Circles Model - Solikha, Mar'atus; Setiawan, FIrman (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2023)
The purpose of this research is to find out the three circless model of the revitalization of ZIS fund reform at BAZNAS Sidoarjo Regency as an effort to increase welfare and alleviate poverty. Qualitative descriptive is a type of research methodology used in this study. The author collects data using observation and interview methods. Meanwhile, descriptive data analysis techniques are used to show data, reduce, and draw conclusions. From the results of this study, it can be concluded that BAZNAS of Sidoarjo Regency implements revitalization with the concept of the three circless model to alleviate poverty in the Muslim community of Sidoarjo. This is evidenced by the existence of a good relationship between muzaki, amil, and mustahik in the management of ZIS. BAZNAS Sidoarjo Regency conducts outreach in various forms and is widely publicized, in collaboration with all stakeholders involved. BAZNAS Sidoarjo Regency has also set up Zakat Collector Units (UPZ) in various locations so they can be reached easily. BAZNAS Sidoarjo Regency cooperates with the Regent to urge government agencies and State Civil Apparatuses (ASN) to become muzakis and channel their ZIS through BAZNAS Sidoarjo Regency through a Circular Letter (SE) of the Regent of Sidoarjo. BAZNAS Sidoarjo Regency empowers mustahik with various economic, educational and productive work programs that will grow mustahik's income.